Long-Term Clinical Outcomes After Femtosecond Laser-Assisted Pterygium Excision - Rui-Pin Fan, Kenric; Liu, Yu-Chi; Fuest, Matthias; Ong, Hon Shing; Htoon, Hla Myint; Ang, Marcus; Mehta, Jodhbir S (Cornea, 2025)
To report the long-term recurrence and complication rates after femtosecond laser-assisted pterygium excision surgery (FLAPS) with conjunctival autograft surgery. Single-center retrospective study of consecutive cases of primary nasal and/or temporal pterygia who underwent primary pterygium excision surgery with femtosecond laser-assisted conjunctival autograft. All subjects underwent manual pterygium excision, followed by femtosecond laser (Femto LDV Z8)-assisted conjunctival autograft surgery and with follow-up duration up to 5 years. Recurrence was defined as appearance of secondary pterygium at the same location. All complications intra- and postoperative were recorded. Primary outcome measure was postoperative pterygia recurrence, and secondary outcomes assessed were the intra- and postoperative complication rates associated with FLAPS. We included 277 sequential FLAPS performed from September 2016 to September 2024. At baseline, mean (SD) age was 62.8 years (13.9); 183 males (66.1%); mean best-corrected visual acuity (BCVA) logMAR 0.23 [0.29]. A total of 200 (72.2%) were of Chinese ethnicity, with 3 (1.2%), 14 (4.9%), and 60 (21.6%) being Indian, Malay, or others. Recurrence was seen in 2/277 patients (0.72%) at 12 and 21 months, respectively, both of which were nasal pterygia, because of glue failure, but declined repeat excision surgery. There were no differences in postoperative BCVA, applanation duration, graft depth, or graft area between the groups. Cox regression analysis showed no significant association between pterygia grade or side with recurrence. Overall 5 years probability to be recurrence free was 99.20%. Five patients (1.8%) experienced dry eyes postoperatively. No intraoperative complications were seen. Primary pterygium excision with femtosecond laser-assisted conjunctival autograft results in low rates of recurrence and complications.